GE_GERICHTE A/1134/2015 vom 18. März 2016 - GE Cour de justice (2016)
Recours au TF interjeté par le plaignant le 28 septembre 2015, rejeté par arrêt du 18 mars 2016 ( | LP.132.1; LP.132.3; OPC.1.1; OPC.1.3; OPC.3; OPC.6; OPC.8.2; OPC.9; OPC.10; OPC.12; CC.609